Mechanisms of social connection : from brain to group - Mikulincer, Mario; Shaver, Phillip R. (Herzliya series on personality and social psychology., 2014)
"Why are human beings so eager to form social bonds, and why do they suffer so grievously when those bonds are disrupted or broken? How does a person overcome fear of rejection and distrust to become emotionally invested in and attached to others? How do we become identified with other members of a social group to the extent that we include them in our self-concept and rely on them to supply our sense of value? Why do they contribute so powerfully to our sense of meaning and our feelings of vitality, on the one hand, and-at times-to our anguish and despair, on the other? What neural and hormonal processes are involved in the formation and maintenance of social bonds? How do our social experiences in infancy and childhood influence our relational behavior and the quality of our social bonds in adulthood? How are our social connections influenced by biological and evolutionary processes and sociocultural contexts? These important questions about human connections have attracted the attention of researchers from diverse disciplines, such as social psychology, developmental psychology, communication studies, sociology, and neuroscience. But there is too little dialogue between the different disciplines, and this has resulted in a lack of integration of insights and findings. In the first four volumes of our Herzliya Series on Personality and Social Psychology, we focused on prosocial motives, emotions, and behavior; aggression, violence, and their effects; morality ("good and evil"); and existential concerns such as mortality, meaning, and freedom. In this, the fifth volume, we deepen our analysis of human social behavior by surveying some of the latest developments in theory and research concerning the physiological and psychological mechanisms underlying the formation of social connections at neural, dyadic, and group levels. We do this with the entire human life span in mind, beginning with infant₆parent relationships. This new volume contains 21 chapters organized into four main sections: the brain level (focusing on the neural underpinnings of social connections and the hormonal processes that contribute to forming connections); the developmental level (focusing especially on child-parent relationships); the dyadic relationship level (focusing especially on romantic and marital relationships); and the group level (considering both evolutionary and physiological bases of group processes). Each section describes state-of-the-art theories and research from the disciplines of social psychology, developmental psychology, and social neuroscience. The chapter authors, all experts in their fields, generously agreed to come to Herzliya and deliver lectures at the 2012 Herzliya Symposium on Personality and Social Psychology. They participated in hours of formal lectures and discussions, spent many informal hours together, and then returned home and prepared chapters based on the lectures and discussions. The meeting was cohosted by the two editors of this volume. We worked with the chapter authors to make the resulting book as accessible, coherent, and readable as possible so it would be suitable for researchers and application oriented professionals as well as for university classes and the educated public. The book provides a lively, engaging, readable, and up-to-the-moment review of social psychological, developmental, and neuroscientific approaches to understanding the formation and quality of social connections across the life span"--Preface. (PsycINFO Database Record (c) 2013 APA, all rights reserved).